Between Responsibility and Freedom: The Fundamental Role of Ethics in Times of Crisis - Remaud, Emilie; Bouguet, Morgan; Marignac, Geneviève (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
At the beginning of the second wave of COVID-19, on November 7, 2020, the conference “Questions d’éthique” was held at the Lieu Unique in Nantes (France). Prof. Axel Kahn’s presentation focused on the ethical perspective of the relations between information and media, researchers and clinical trials, individual liberty and health democracy, but also the urgency of care, patient triage and confinement. Starting from the indispensable character of “ethics in times of crisis”, the title of his talk, he analyzed his practice through the prism of liberty and responsibility.